Tanggung Jawab Hukum Dan Etika Kesehatan - Juwita Suma (Universitas Negeri Gorontalo, 2009)
Health is one of main yardstick of national development and prosperity a nation. Unhappily knowledge about health has not is national policy that have been involve public and decision maker. To realize degree of optimal health for every people, required low support for implementation of various activities in health area. Shortly to realize degree of optimal health for every people continually, required seriously attention for the implementation of national development which with vision of health. Basically health law convergent at rights to healthcare as social base rights. Relates to thing which has been explained before, protection of law to patient and also health officer shall be arranged in separate law. This special arrangement required for both of patient and health officer ones. Kata Kunci: Tanggungjawab, Hukum, Etika Profesi, Kesehatan.